Pengaruh brand image dan health consciousness terhadap purchase intention produk multigrain: Mediasi consumer attitude - Anastasia, Anastasia; Tjokrosaputro, Miharni (Universitas Tarumanagara, 2025)
Health consciousness becomes an important topic to be focus on these days. Indonesian becomes more aware towards their health after pandemic. Due to the issues of low fulfillment in daily intake of dietary fiber, hence the study about the factor affecting purchase intention of high fiber multigrain product, becomes an important to be performed. This study was conducted in Indonesia, with 220 data which was collected through Google Form Questionnaire. Data analysis was performed using PLS-SEM method. Result showed that Consumer Attitude has a partial mediating effect between both Brand Image and Health Consciousness towards Purchase Intention of multigrain product. There is positive and significant direct effect of Brand Image, Health Consciousness and Consumer Attitude towards Purchase Intention. Broad implication of this study includes the evaluation and improvement of factors affecting Purchase Intention of multigrain product, increase the purchase intention and solving the issue of dietary fiber’s fulfillment in Indonesia. Kesadaran Kesehatan menjadi topik penting untuk fokus dibahas pada hari-hari ini. Masyarakat di Indonesia menjadi lebih sadar akan kesehatannya setelah pandemi. Dikarenakan adanya masalah tentang rendahnya tingkat kecukupan serat harian, maka penelitian untuk mengetahui faktor yang mempengaruhi Niat Membeli produk tinggi serat menjadi penting untuk dilakukan. Penelitian ini dilakukan di Indonesia, dengan 220 data yang dipakai dari pengisian Kuesioner Google Form. Data Analisis dilakukan dengan menggunakan PLS-SEM. Hasil menunjukkan bahwa Sikap Konsumen memediasi secara parsial hubungan Citra Merek dan Kesadaran Kesehatan terhadap Niat Membeli produk Multigrain. Terdapat adanya pengaruh langsung yang positif dan signifikan antara Citra Merek, Kesadaran Kesehatan dan Sikap Konsumen terhadap Niat Membeli. Implikasi hasil studi ini secara luas adalah untuk mengevaluasi dan meningkatkan faktor yang mempengaruhi Niat Membeli Produk Multigrain sehingga Niat Membeli dapat ditingkatkan dan masalah pemenuhan kecukupan serat harian dapat diatasi.